The role of blood pressure variability indicators combined with cerebral blood flow parameters in predicting intraventricular hemorrhage in very low birth weight preterm infants - Jiang, Lijun; Yu, Qian; Wang, Fudong; Wu, Mingfu; Liu, Feng; Fu, Mingfeng; Gao, Junyan; Feng, Xing; Zhang, Longfeng; Xu, Zhenxing (Frontiers in Pediatrics, 2023)
Background: Hemodynamic instability is the main factor responsible for the development of intraventricular hemorrhage (IVH) in premature newborns. Herein, we evaluated the predictive ability of blood pressure variability (BPV) and anterior cerebral artery (ACA) blood flow parameters in IVH in premature infants with gestational age (GA) ≤32 weeks and birth weight (BW) ≤1500 g.Preterm infants with GA ≤32 weeks and BW ≤1500 g admitted to the neonatal intensive care unit (NICU) from January 2020 to January 2023 were selected as the research subjects. All preterm infants were admitted within 1 h after birth, and systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial blood pressure (MABP) were monitored at 1-h intervals. The difference between maximum and minimum values (max-min), standard deviation (SD), coefficient of variation (CV), and successive variation (SV) were used as BPV indicators. On the 1st, 3rd, and 7th day after birth, transcranial ultrasound examination was performed to screen for the occurrence of IVH. On the 24±1h after birth, systolic velocity (Vs), diastolic velocity (Vd), and resistance index (RI) of the ACA were measured simultaneously. Preterm infants were divided into the IVH group and non-IVH group based on the results of transcranial ultrasound examination, and the correlation between BPV indicators, ACA blood flow parameters, and development of IVH was analyzed.Results: A total of 92 premature infants were enrolled, including 49 in the IVH group and 43 in the non-IVH group. There was no statistically significant difference in baseline characteristics such as This is a provisional file, not the final typeset article BW, GA, sex, and perinatal medical history between the two groups of preterm infants (P>0.05). The SBP SD (OR: 1.480, 95%CI: 1.020-2.147) and ACA-RI (OR: 3.027, 95%CI: 2.769-3.591) were independent risk factors for IVH in premature newborns. The sensitivity and specificity of combined detection of SBP SD and ACA-RI in predicting IVH were 61.2% and 79.1%, respectively.High BPV and ACA-RI are related to IVH in premature infants with GA ≤32 w and BW ≤1500 g. Combined detection of SBP SD and ACA-RI has a certain predictive effect on early identification of IVH.